Pendidik Dinamis dan Inovasi dalam Dunia Pendidikan - Asef Umar Fakhruddin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Education is the most effective mean to internalize democracy, pluralism, and inclusive values. This kind of education can accommodate every difference. Meanwhile, education that emphasizes internalization of divine values will become solution to various problem of this nation. Dynamic education will made us understand substance and meaning of everything.Â This paradigm only can be manifested by teacher that have dynamic attitude, on viewing difference, on noticing studentâ€™s character and need, and to face life and this world.Â